(untitled) (Physical Education, Health and Social Sciences, 2025)
The current study was conducted to examine the effects of high intensity interval training (HIIT) to be applied at morning and evening on some selected parameters of colleges’ badminton players. A total of 45 male college’s badminton players between the age of 18-24 years was participated in the study. Participants was divided into two groups, Experimental Group (EG) n=30 and Control Group (CG) n=15 based on the aerobic fitness assessment results. The EG was further divided into Morning Group A and Evening Group b. EG was given prescribed training, while CG was remaining as usual. Data was collected two times; T1 pre-test and T2 post-test after eight weeks. T-test and repeated measure ANOVA was applied to measure the statistically significant differences between pre- and post-test results.